Surgical Versus Percutaneous Coronary Revascularization for Multivessel Disease in Diabetic Patients With Non–ST-Segment–Elevation Acute Coronary Syndrome: Analysis From the Acute Catheterization and Early Intervention Triage Strategy Trial. (June 2015) - Ben-Gal, Yanai; Mohr, Rephael; Feit, Frederick; Ohman, E. Magnus; Kirtane, Ajay; Xu, Ke; Mehran, Roxana; Stone, Gregg W.
Abstract : Background—: The preferred revascularization strategy for diabetic patients with acute coronary syndromes and multivessel coronary artery disease is uncertain. We evaluated the outcomes of diabetic patients with moderate and high-risk acute coronary syndrome and multivessel disease managed with percutaneous coronary intervention (PCI) versus coronary artery bypass grafting (CABG). Methods and Results—: Among 13 819 moderate and high-risk acute coronary syndrome patients enrolled in the Acute Catheterization and Early Intervention Triage Strategy (ACUITY) trial, 1772 diabetic patients had multivessel disease with left anterior descending artery involvement and were managed by PCI (n=1349) or CABG (n=423). Propensity scoring was applied to adjust for differences in baseline clinical and angiographic characteristics, yielding a total of 326 matched patients (163 managed by PCI and 163 managed by CABG). At 30 days, treatment with PCI compared with CABG was associated with lower rates of major bleeding (15.3% versus 55.6%; P <0.0001), blood transfusions (9.2% versus 43.2%; P <0.0001), and acute kidney injury (13.4% versus 33.6%; P <0.0001), but more unplanned revascularization procedures (6.9% versus 1.9%; P =0.03). At 1 year PCI was associated with higher rates of repeat revascularization procedures (19.5% versus 5.2%; P =0.0001), with nonsignificantly different rates of myocardial infarction, stroke, and death at either 30 days or 1 year. Conclusions—: In the large-scale ACUITY trial, diabetic patients with acute coronary syndrome and multivessel disease treated with PCI rather than CABG had less bleeding and acute kidney injury, greater need for repeat revascularization procedures, and comparable rates of myocardial infarction, stroke, and death through 1-year follow-up. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00093158.